Pendidikan Multikultural Dalam Penanaman Misi Ramah Kemanusiaan Bagi Anak Oleh Komunitas Pelayan Anak Sangkakala (Kopelans) - Sari, Dwi Novita; Nugroho, Fibry Jati (Fakultas Ilmu Keguruan dan Pendidikan, Universitas Kristen Indonesia, 2022)
This article reviews the importance of planting a humanitarian-friendly mission for children as a form of preventive effort from the emergence of selfish attitudes as a result of the onslaught of modernization and a social media lifestyle. The urgency of this research is that if a humanitarian mission is not instilled in children, the next generation will lose character, so the purpose of education, namely to develop the potential of students and form human beings who believe and have noble character (based on Law No. 20 of 2003 concerning National Education System) cannot be realized. Therefore, it is crucial to study this matter. Kopelans, as a community engaged in children's services scope, uses the puppet stage media in teaching a humanitarian-friendly mission for children. The children served are multicultural, specifically from different social, ethnic, and religious statuses. This study uses a qualitative approach using analytical-descriptive methods that can closely describe what is happening in the field. The data collection tools used are literature studies, interviews, and observations. The result is that Kopelans use multicultural education as the basis for inculcating moral values that are a condition of truth for inculcating a humanitarian-friendly mission for children. Humanity-friendly missions are crucial to be ingrained from a young age. Humanity-friendly mission helps children understand tolerance, thereby reducing selfishness. The humanitarian-friendly mission is instilled through the puppet stage media can be accepted by children.